Keluarga dalam Interaksi Misi Pendidikan (di Kelurahan Sungguminasa, Kab. Gowa) - Hamdi Arsyad; Nur Azlin; Sam'un Mukramin; Arham Arham; Ayatullah Ayatullah (Departement of Mathematics Education, 2023)
In an effort to produce a strong and quality next generation, it requires consistent effort from parents in carrying out the task of caring for and educating children both physically and spiritually. In society, the family is the smallest miniature whose role is very large. This very large role is due to the fact that the family has a very important function in the continuity of the child's educational life where this task is the obligation of parents as a family which is the first home for children in an effort to improve the quality of children's growth. In the Islamic view, children are a mandate from Allah, therefore in the context of education, interaction between parents and children is needed before the child reaches adulthood, such as having to fully protect and guide, and is also responsible for saving the family through education. Keywords: Family, Interaction, Education.